Growth and endocrine function in steroid sensitive nephrotic syndrome. Issue 5 (May 1988) - Rees, L; Greene, S A; Adlard, P; Jones, J; Haycock, G B; Rigden, S P; Preece, M; Chantler, C
Abstract : Longitudinal height data and physical development were assessed in 29 boys and 12 girls taking long term steroid treatment for steroid sensitive nephrotic syndrome. Growth in both boys and girls, assessed by changes in height standard deviation score (delta Ht SDS), worsened significantly with chronological age. There was a significant negative correlation between delta Ht SDS and duration of treatment in boys, but not in girls. There was no correlation between delta Ht SDS and relapse rate or the use of cyclophosphamide. In the boys, Ht SDS decreased significantly only after the age of 10 years and was associated with delay in the appearance of secondary sexual characteristics. Eight adolescent boys were assessed endocrinologically by an overnight hormone profile. Blunting of the pulsatility of growth hormone and gonadotrophins was seen in six. Normal profiles were seen in two subjects who were both off steroid treatment at the time of study. Abnormal endocrine function in adolescent boys treated long term for steroid sensitive nephrotic syndrome corresponded with the clinical picture of delayed onset of puberty, which accounted for severe growth retardation in a substantial proportion of subjects.